Molecular evolution of the seventh-pandemic clone of Vibrio cholerae and its relationship to other pandemic and epidemic V. cholerae isolates. - Karaolis, D K (1994)
Genetic variation and molecular evolution within the seventh-pandemic clone of Vibrio cholerae O1 and its relationship to other V. cholerae isolates were examined by studying 58 clinical isolates that were epidemiologically unassociated and isolated from patients in different countries over 62 years (1931 to 1993). The sample consisted of 45 isolates from the seventh cholera pandemic (1961 to the present), 3 from the sixth pandemic, 3 from sporadic El Tor outbreaks prior to the seventh pandemic, 2 from the U.S. Gulf Coast, and 5 O139 Bengal isolates. Ribotyping detected 11 polymorphic restriction sites within the seventh-pandemic isolates and showed major differences in ribotypes in comparison with sixth- and pre-seventh-pandemic isolates. O139 isolates were very similar to isolates from the start of the seventh pandemic, differing at only two sites. The majority of seventh-pandemic isolates fall into two groups, the first present from 1961 to the present and found only in Asia and the second arising in 1966 and spreading worldwide. Both groups underwent change over time, allowing a provisional estimate for the nucleotide substitution rate within the seventh pandemic clone.